To intubate or not to intubate? Predictors of inhalation injury in burn‐injured patients before arrival at the burn centre. (27th August 2020) - Dyson, Kylie; Baker, Paul; Garcia, Nicole; Braun, Anna; Aung, Myat; Pilcher, David; Smith, Karen; Cleland, Heather; Gabbe, Belinda
Abstract: Objective: Inhalation injury occurs in approximately 10–20% of burn patients and is associated with increased mortality. There is no clear method of identifying patients at risk of inhalation injury or requiring intubation in the pre‐hospital setting. Our objective was to identify pre‐burn centre factors associated with inhalation injury confirmed on bronchoscopy, and to develop a prognostic model for inhalation injury. Methods: We analysed acute admissions from the Victorian Adult Burns Service and Ambulance Victoria electronic patient care records for 1 July 2009 to 30 June 2016. We defined inhalation injury as an Abbreviated Injury Scale of >1 on bronchoscopy. A multivariable logistic regression prediction model was developed based on pre‐burn centre factors. Results: Emergency medical services transported 1148 patients who were admitted to the burn centre. The median age of patients was 39 years and most patients had <10% total body surface area (%TBSA) burned. The prevalence of confirmed inhalation injury was 11%. Increasing %TBSA burned, flame, enclosed space, face burns, hoarse voice, soot in mouth and shortness of breath were predictive of inhalation injury. The model provided excellent discrimination (area under curve 0.87, 95% confidence interval 0.84–0.91). A lower proportion of patients intubated at a non‐burn centre had an inhalation injury (33%) compared to patients intubated by emergency medical services (54%) and in the burn centre (58%). Conclusions: A model to predict inhalation injury in burn‐injured patients was developed with excellent discrimination. This model requires prospective testing but could form an integral part of clinician decision‐making. Abstract : Our objective was to identify pre‐burn centre factors associated with inhalation injury confirmed on bronchoscopy, and to develop a prognostic model for inhalation injury. Increasing percentage of total body surface area burned, flame, enclosed space, face burns, hoarse voice, soot in mouth and shortness of breath were predictive of inhalation injury.